IMPLEMENTASI STRATEGI GUIDED WRITING PROCESS PADA KETERAMPILAN MENULIS TEKS WAWANCARA SISWA KELAS V SEKOLAH DASAR - Izza, Tsania Rohmatul; Oktaviani, Rizka Nur (STKIP Melawi, 2025)
Abstract:. This study uses a descriptive qualitative approach to explain how the Guided Writing Process (GWP) strategy is applied to the interview text writing skills of Grade V elementary school students and how GWP has an impact on their interview text writing skills. The students involved in this study are grade V elementary school students. Data collection is carried out through observation, interviews, and documentation. Data analysis was carried out in a qualitative descriptive manner. The results of the study show that the application of the Guided Writing Process (GWP) strategy to the interview text writing skills of grade V elementary school students has been carried out very well. Students showed excellent results in various elements of assessment, such as systematically writing reports, using capital letters, punctuation, standard vocabulary, independent attitudes, and writing effective sentences. However, some students need additional help, such as choosing vocabulary and writing capital letters. Keywords: Guided Writing Process, interview text writing, writing regularity Abstrak: Penelitian ini menggunakan pendekatan kualitatif deskriptif untuk menjelaskan bagaimana strategi Guided Writing Process (GWP) diterapkan pada keterampilan menulis teks wawancara siswa Kelas V SD dan bagaimana GWP berdampak pada keterampilan menulis teks wawancara mereka. Siswa yang terlibat dalam penelitian ini adalah siswa kelas V SD. Pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Analisis data dilakukan secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa penerapan strategi Guided Writing Process (GWP) pada keterampilan menulis teks wawancara siswa kelas V SD telah dilakukan dengan sangat baik. Siswa menunjukkan hasil yang sangat baik dalam berbagai elemen penilaian, seperti menulis laporan dengan sistematis, menggunakan huruf kapital, tanda baca, kosa kata baku, sikap mandiri, dan menulis kalimat efektif. Namun, beberapa siswa memerlukan bantuan tambahan, seperti memilih kosa kata dan menulis huruf kapital. Kata Kunci: Proses Penulisan Terbimbing, Teks Wawancara, Keterampilan Menulis